Copaiba oil-resin (Copaifera reticulata Ducke) modulates the inflammation in a model of injury to rats' tongues - Francisco Bruno Teixeira; Raíra de Brito Silva; Osmar Alves Lameira; Liana Preto Webber; Roberta Souza D'Almeida Couto; Manoela Domingues Martins; Rafael Rodrigues Lima (BMC, 2017)
Abstract Background The regeneration of integrity and tissue homeostasis after injury is a fundamental property and involves complex biological processes fully dynamic and interconnected. Although there are medications prescribed to accelerate the process of wound healing by reducing the exaggerated inflammatory response, comes the need to search for different compounds of Amazonian biodiversity that can contribute to the acceleration of the healing process. Among these products, the copaiba oil-resin is one of the most prominent feature in this scenario, as they have been reported its medicinal properties. Methods Aiming to evaluate the anti-inflammatory and healing effect of copaiba oil-resin (Copaifera reticulata Ducke) in transfixing injury of rats' tongues first proceeded up the copaiba oil-resin oral toxicity test in 5 male mice to stipulate the therapeutic dose which was established at 200 mg/kg/day. Then it was induced transfixing injury in a total of 15 Wistar rats. The animals were randomly divided into three groups based on the treatment: control group, dexamethasone group and copaiba oil-resin group. After 7 days of treatment, histological slides stained with hematoxylin and eosin was prepared. Immunohistochemistry for CD68 (macrophage marker) was performed and analyzed by the cell counter Image J. Results The acute toxicity test showed that the oil-resin copal has low toxicity. Furthermore, copaiba oil-resin therapy modulates the inflammatory response by decreasing the chronic inflammatory infiltrate, edema and specifically the number of macrophages. Conclusions The results indicate the potential of the Amazon region and showed up relevant because therapy with this extract modulates the inflammatory process.